The Bidirectional Relation between Parental Rejection and Internalizing and Externalizing Behaviors from Age 10 To 12 in Filipino Families - Tan, Jill Ann Therese (Archīum Ateneo, 2020)
The present study examined the bidirectional relation of maternal and paternal rejection, and internalizing and externalizing behaviors in Filipino families. Data were taken from the Philippine data set of the third and fifth wave of a longitudinal study: Parenting Across Cultures. The children sample (N = 105, 49% female) were age 10 (Mage = 10.52) at wave 3 and age 12 (Mage = 12.57) at wave 5 in the data analyzed for the current study. Child reports of internalizing and externalizing behavior and parent reports of their rejection behaviors were used in the analysis. Data were analyzed through autoregressive, cross-lagged path models using EQS software. Four models were analyzed: (1) bidirectional relations between maternal rejection and child internalizing behaviors, (2) bidirectional relations between maternal rejection and child externalizing behaviors, (3) bidirectional relations between paternal rejection and child internalizing behaviors, and (4) bidirectional relations between paternal rejection and child externalizing behaviors. Results showed stability for all variable behaviors from age 10 to age 12. Bidirectional relations between parental rejection and child behaviors were not found in any of the models. However, child externalizing behaviors at age 10 was a significant predictor of maternal rejection at age 12, suggesting that children play a role in the maternal behaviors. Parenting interventions may harness this information to create programs that include awareness of how their children’s difficult behaviors influence the way they react. Programs may strengthen conscious parenting where parents are trained to respond in a regulated manner to challenging child behaviors.